2015
DOI: 10.4236/ojped.2015.53038
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Neural Tube Defects: Moroccan Study 2008-2011

Abstract: Background: Neural tube defects have a considerable importance because they can be prevented by supplementing Folic acid & Vitamin B12 during periconceptional period and fortification of staple foods. In Morocco, the Ministry of Health launched a national program for fortification of flour with folic acid. Our goal should be to evaluate the prevalence of neural tube defects after fortification. Description: This is a retrospective descriptive at the National Reference Centre for Nutrition and Neonatology of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…38 39 Studies conducted in Morocco, Tunisia, Algeria, the Democratic Republic (DR) of Congo, Egypt, Cameron, Ghana and Libya were also identified. [42][43][44][45][46][47][48][49] All studies included in this review were facility-based studies, published in the year between 1992 and 2020. South Africa (started fortification in 2003), Nigeria (in 2002), Tanzania (in 2011) and Kenya (in 2012) have mandatory folic acid fortification with Wheat Flour and Maize Flour.…”
Section: Characteristics Of the Original Studiesmentioning
confidence: 99%
“…38 39 Studies conducted in Morocco, Tunisia, Algeria, the Democratic Republic (DR) of Congo, Egypt, Cameron, Ghana and Libya were also identified. [42][43][44][45][46][47][48][49] All studies included in this review were facility-based studies, published in the year between 1992 and 2020. South Africa (started fortification in 2003), Nigeria (in 2002), Tanzania (in 2011) and Kenya (in 2012) have mandatory folic acid fortification with Wheat Flour and Maize Flour.…”
Section: Characteristics Of the Original Studiesmentioning
confidence: 99%
“…All research published between 1982 and 2022 that meet the criteria were eligible. There were forty cross-sectional studies (68.97%) [ 8 10 , 14 – 18 , 23 , 24 , 26 , 27 , 31 37 , 40 44 , 47 – 49 , 52 , 57 63 , 65 – 68 ], eight cohort studies (13.79%) [ 17 , 29 , 38 , 39 , 46 , 55 , 56 , 64 ], and ten case-control studies (17.24%) [ 19 22 , 28 , 30 , 32 , 50 , 51 , 54 ] in this analysis. Furthermore, 19 (32.76%) of the studies were rated as high quality.…”
Section: Resultsmentioning
confidence: 99%
“…However, this multicenter study excluded stillbirths, fetal deaths in utero after 22 weeks' amenorrhea, and medical terminations of pregnancy. Other local Moroccan studies have shown that the annual prevalence of NTDs [ 30 ] has decreased significantly, from 2.17 in 2008 to 1.21/1000 births in 2011. In 2021, another Moroccan study [ 31 ] showed that the prevalence rate of NTDs was 1 per 1000 LBs in Rabat.…”
Section: Discussionmentioning
confidence: 99%